2020
DOI: 10.1101/2020.12.02.20237974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of photobiomodulation therapy combined with static magnetic field (PBMT-sMF) in patients with severe COVID-19 requiring intubation: a pragmatic randomized placebo-controlled trial

Abstract: BackgroundPhotobiomodulation therapy (PBMT) when used isolated or combined with static magnetic field (PBMT-sMF) has been proven benefits on skeletal muscle increasing performance and reducing fatigue, increasing oxygen saturation, and modulating inflammatory process. However, it is unknown whether the effects observed with this therapy on respiratory muscles will be similar to the effects previously observed on skeletal muscles.ObjectiveWe aimed to investigate whether PBMT-sMF is able to decrease the length o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Although small amounts of heat are produced during PBM, the process is photochemical not thermal, invoking biophysical mechanisms offering therapeutic outcomes that thermotherapy cannot. [ 11 ] Reported PBM benefits include reduced tissue inflammation[ 12 ], [ 13 ], [ 14 ] and dyspnea, [ 15 ] improved circulation,[ 16 ] decreased pain[ 17 ] and accelerated recovery. [ 18 ], [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although small amounts of heat are produced during PBM, the process is photochemical not thermal, invoking biophysical mechanisms offering therapeutic outcomes that thermotherapy cannot. [ 11 ] Reported PBM benefits include reduced tissue inflammation[ 12 ], [ 13 ], [ 14 ] and dyspnea, [ 15 ] improved circulation,[ 16 ] decreased pain[ 17 ] and accelerated recovery. [ 18 ], [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although small amounts of heat are produced during PBM, the process is photochemical not thermal, invoking biophysical mechanisms offering therapeutic outcomes that thermotherapy cannot. [11] Reported PBM benefits include reduced tissue inflammation [12], [13], [14] and dyspnea, [15] improved circulation, [16] decreased pain [17] and accelerated recovery. [18], [19] PBM is also found to interfere with a pathogen's ability to replicate [20] through innate immune response (via reactive ion species, [ROS]) and over longer intervals by regulating adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%
“…In a published study that included 45 patients with 18 having established criteria for a ICUAW diagnosis, the hand grip strength (HGD) and the global muscle strength (MRC score) showed good agreement with each other (100% accuracy; Kappa coefficient = 1; p < 0.001) [39]. De Marchi et al [21] also reported interesting results when they applied PBMT combined with a static magnetic field (PBMT-sMF) in ICU patients. Their focus was on severe COVID-19 patients requiring intubation, and their results showed some differences to our study, because they performed the therapy once a day until either ICU discharge or death.…”
Section: Discussionmentioning
confidence: 94%
“…These effects include increased protein synthesis (muscle hypertrophy), increased synthesis of the muscle energy sources ATP (adenosine triphosphate) and glycogen, and greater resistance to oxidative stress, which produce increased strength and fatigue resistance [11,18]. However, few studies have investigated the effects of PBMT in populations in hospital or intensive care [6,[19][20][21][22]. Moreover, the literature does not contain properly controlled randomized trials of the effects of PBMT in critically ill patients or those admitted to ICUs.…”
Section: Introductionmentioning
confidence: 99%
“…Another technique that can be useful in this scenario is PBMT when used alone or combined with the static magnetic field (PBMT-sMF). In a study, with patients with severe COVID-19 that required mechanical ventilation were randomly assigned to receive PBMT-sMF (six sites on the lower chest—189 J in total and two sites in the neck area—63 J in total) or PBMT-sMF placebo daily for the entire ICU stay, it was noted that PBMT-sMF was able to improve some ventilatory parameters, in addition to the infectious process, and immune response [ 36 ]. Thus, these techniques suggest that treatment with PBMT-sMF or LLLT may reduce the burden on the hospital and health systems and the use of scarce health care resources during this pandemic [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%